Strategic behavior of non-expected utility players in games with payoff uncertainty - Florian Kauffeldt (University of Heidelberg, Department of Economics, 2016)
This paper investigates whether the strategic behavior of expected utility players differs from that of non-expected utility players in the context of incomplete information games where players can choose mixed strategies. Two conditions are identified where uncertainty-averse non-expected utility players behave differently from expected utility players. These conditions concern the use of mixed strategies and the response to it. It is shown that, if and only if these conditions fail, nonexpected utility players behave as if they were expected utility players. The paper provides conditions, in terms of the payoff structure of a game, which are necessary and sufficient for behavioral differences between expected and non-expected utility players. In this context, games are analyzed that are especially relevant for the design of experiments.
urn:nbn:de:bsz:16-heidok-205711
Keywords: 330; Non-expected utility; Incomplete information games; Uncertainty aversion; Mixed strategies; Strategic behavior; Entscheidung unter Unsicherheit; Erwartungsnutzen; Unvollkommene Information; Normalformspiel